2014
DOI: 10.1080/07325223.2014.992270
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Leadership Preparation in Counselor Education Doctoral Students Who Are Members of the American Counseling Association in CACREP-Accredited Programs

Abstract: The researchers examined the perceived leadership training of counselor education doctoral students (N ¼ 228) regarding their leadership preparedness. The results indicated that the majority of the participants believed that they are receiving the training that will prepare them to be leaders in the domains of clinical counseling, research, teaching, clinical supervision, writing and publishing, professional advocacy, leading and managing people, and motivating others to accomplish a mission. Conversely, the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Third, many counselor educators rise to leadership positions within the counseling field and may influence the professional identity of others and the profession on a macrolevel. Leadership training is part of counselor education programs (Lockard, Laux, Ritchie, Piazza, & Haefner, ). Many professionals describe engagement through leadership as a core aspect of professional identity (Myers et al, ).…”
Section: Roles Of Counselor Educators In Development Of Counselor Promentioning
confidence: 99%
“…Third, many counselor educators rise to leadership positions within the counseling field and may influence the professional identity of others and the profession on a macrolevel. Leadership training is part of counselor education programs (Lockard, Laux, Ritchie, Piazza, & Haefner, ). Many professionals describe engagement through leadership as a core aspect of professional identity (Myers et al, ).…”
Section: Roles Of Counselor Educators In Development Of Counselor Promentioning
confidence: 99%
“…Hill and Friedman (2019) suggested that counseling leadership development is "contingent on a robust and comprehensive interaction with the profession of counselor education" (p. 174). Scholars have identified professional role socialization, mentoring, service learning, emerging leader programming, and apprenticeship models as pathways for counseling leadership development (Gibson, 2016;Gibson et al, 2018;Lockard et al, 2014;Storlie et al, 2015;Peters et al, in press). Reflecting the importance of leadership as part of counselor professional identity, Lanning (1986) extended the discrimination model to include this as a fourth foci area for professional behavior, without much uptake over the past 25 years.…”
Section: Leadership Developmentmentioning
confidence: 99%
“…Leadership is integral to counselor identity and practice (Council for Accreditation of Counseling and other Related Education Programs, [CACREP], 2015;Paradise et al, 2010). CACREP has identified leadership development as one of five primary foci for doctoral programs (Lockard et al, 2014), and has prioritized its development in the specialty areas as well. These changes have led to the supervision of counseling leadership as a viable pedagogical practice, which has only been explored in the past decade (Glosoff et al 2012;Peters & Luke, in review).…”
Section: Leadership Developmentmentioning
confidence: 99%
“…The entire research study has got a total of 300 sample size to execute the concealed phenomenon. Lockard III, Laux, Ritchie, Piazza, and Haefner (2014), had conducted an empirical study on the academic performance of students by taken medical students as respondents. Moreover, they have define the sampling criteria like as 150 => poor; 200 => Not bad; 300 => Good; 500 => very good; 750 => Excellent and 1000 and above => Too Excellent.…”
Section: Sample Size and Sampling Techniquementioning
confidence: 99%